The Emergency Level Algorithm Uses the National Early Warning System (News) Method for Non-Rebreathing Mask Oxygen Therapy Patients - Kuzzairi; Taufiqurrahman; Endang Fauziyah Susilawati (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
The mixed gas pressure theory states that if the pressure of one gas in a gas mixture increases, the partial pressure of the other gas will decrease. Increasing the oxygen concentration in the non-rebreathing mask will reduce the partial pressure of CO2, so that it can reduce PaCO2 and maintain a high PaO2. Researchers want to know the level of emergency by looking at the effectiveness of administering O2 on hemodynamic status using the NEWS (National Early Warning System) method, where currently only O2 saturation and arterial blood gas analysis values ​​are often used to evaluate, without any scoring, with an action algorithm according to the emergency level scoring report. This research is a quasi-experimental one-group pre-post-test design with a one-shot pretest and posttest design on all patients who have respiratory complaints with NEWS score values ​​in the moderate and severe categories in the ICU of Dr. Hospital. Slamet Martodirjo Pamekasan. Sampling uses non-probability purposive sampling. Because the population of this study is infinite, the target sample size is 20 respondents. The emergence of patients in the ICU after receiving the second 6-hour phase of O2 NRM therapy intervention was found by most respondents (55%) in the mild category, and only 20% in the severe category. This means that the number of patients in the critical or high category is much less than after the first 2 hours of therapy, namely 65% ​​to 20% and most of them are already in the mild category after the second 6 hours of O2 therapy. This study concludes that O2 NRM therapy has a significant effect on reducing the level of emergency for the first 2 hours and evaluation for the second 6 hours, resulting in a different emergency algorithm (reducing the level of emergency) for the two evaluation phases with different levels of emergency.